Comparison of cardiac surgery with left atrial surgical ablation vs. cardiac surgery without atrial ablation in patients with coronary and/or valvular heart disease plus atrial fibrillation: final results of the PRAGUE-12 randomized multicentre study - Budera, Petr; Straka, Zbyněk; Osmančík, Pavel; Vaněk, Tomáš; Jelínek, Štěpán; Hlavička, Jan; Fojt, Richard; Červinka, Pavel; Hulman, Michal; Šmíd, Michal; Malý, Marek; Widimský, Petr (European heart journal, 2012)
AIMS: Surgical ablation procedure can restore sinus rhythm (SR) in patients with atrial fibrillation (AF) undergoing cardiac surgery. However, it is not known whether it has any impact on long-term clinical outcomes. METHODS AND RESULTS: This multicentre study randomized 224 patients with AF scheduled for valve and/or coronary surgery: group A (left atrial surgical ablation, n = 117) vs. group B (no ablation, n = 107). The primary efficacy outcome was the SR presence (without any AF episode) during a 24 h electrocardiogram (ECG) after 1 year. The primary safety outcome was the combined endpoint of death/myocardial infarction/stroke/renal failure at 30 days. A Holter-ECG after 1 year revealed SR in 60.2% of group A patients vs. 35.5% in group B (P = 0.002). The combined safety endpoint at 30 days occurred in 10.3% (group A) vs. 14.7% (group B, P = 0.411). All-cause 1-year mortality was 16.2% (A) vs. 17.4% (B, P = 0.800). Stroke occurred in 2.7% (A) vs. 4.3% (B) patients (P = 0.319). No difference (A vs. B) in SR was found among patients with paroxysmal (61.9 vs. 58.3%) or persistent (72 vs. 50%) AF, but ablation significantly increased SR prevalence in patients with longstanding persistent AF (53.2 vs. 13.9%, P < 0.001). CONCLUSION: Surgical ablation improves the likelihood of SR presence post-operatively without increasing peri-operative complications. However, the higher prevalence of SR did not translate to improved clinical outcomes at 1 year. Further follow-ups (e.g. 5-year) are warranted to show any potential clinical benefit which might occur later.
Keywords: recidiva; délka operace; Humans; Electrocardiography; nemoci srdečních chlopní; Female; Aged; výsledek terapie; senioři; lidé; Atrial Fibrillation; Heart Valve Diseases; katetrizační ablace; Postoperative Complications; Postoperative Care; Operative Time; pooperační komplikace; ženské pohlaví; Male; koronární nemoc; pooperační péče; Treatment Outcome; Coronary Disease; Recurrence; mužské pohlaví; prospektivní studie; antikoagulancia; Catheter Ablation; Anticoagulants; fibrilace síní; elektrokardiografie; Prospective Studies